Cochlear Implantation Updates: The Dallas Cochlear Implant Program. - Tobey, Emily A.; Britt, Lana; Geers, Ann; Loizou, Philip; Loy, Betty; Roland, Peter; Warner-Czyz, Andrea; Wright, Charles G. (Journal of the American Academy of Audiology, 2012)
This report provides an overview of many research projects conducted by the Dallas Cochlear Implant Program, a joint enterprise between the University of Texas at Dallas, the University of Texas Southwestern Medical Center, and Children's Medical Center. The studies extend our knowledge of factors influencing communication outcomes in users of cochlear implants. Multiple designs and statistical techniques are used in the studies described including both cross sectional and longitudinal analyses. Sample sizes vary across the studies, and many of the samples represent large populations of children from North America. Multiple statistical techniques are used by the team to analyze outcomes. The team has provided critical information regarding electrode placement, signal processing, and communication outcomes in users of cochlear implants.